1999
DOI: 10.1530/eje.0.1400035
|View full text |Cite
|
Sign up to set email alerts
|

Changes in body composition and leptin levels during growth hormone (GH) treatment in short children with various GH secretory capacities

Abstract: Objective: The aim of this study was to follow changes in body composition, estimated by dual-energy Xray absorptiometry (DXA), in relation to changes in leptin during the first year of GH therapy in order to test the hypothesis that leptin is a metabolic signal involved in the regulation of GH secretion in children. Design and Methods: In total, 33 prepubertal children were investigated. Their mean (S.D.) chronological age at the start of GH treatment was 11.5 (1.6) years, and their mean height was ¹ 2.33 (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…Leptin levels were reduced after GH replacement therapy, and this effect was thought to be secondary to reduction in fat mass32. In contrast, another study found that leptin levels were significantly increased after a single dose of GH and subsequently dropped below the baseline; this observation indicates that GH has a direct regulatory effect on leptin gene expression33.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin levels were reduced after GH replacement therapy, and this effect was thought to be secondary to reduction in fat mass32. In contrast, another study found that leptin levels were significantly increased after a single dose of GH and subsequently dropped below the baseline; this observation indicates that GH has a direct regulatory effect on leptin gene expression33.…”
Section: Discussionmentioning
confidence: 99%
“…These observations illustrate that serum leptin responds differently to hGH in children with CRF, who are GH/IGF-I insensitive but not GH deficient. Indeed, in short children with various GH secretory capacities, the magnitude of decrease in serum leptin during 12 months of hGH treatment has been shown to correlate inversely with endogenous GH secretion [2]. This study suggests that, unlike GHD, basal leptin levels cannot be used as a predictor of response to hGH treatment over the 1st year in children with CRF.…”
Section: Discussionmentioning
confidence: 79%
“…The decrease in serum leptin in GHD has been proposed as a predictor of the growth response to hGH [1,2,3]. In addition to high circulating GH, low GH-binding protein, low-normal insulin-like growth factor-I (IGF-I), reduced free IGF-I, high-normal IGF-II, high IGF-binding protein levels [4,5,6] and elevated serum leptin levels have been reported in children with chronic renal failure (CRF) [7].…”
Section: Introductionmentioning
confidence: 99%
“…While this is in contrast to the results of an IGF-1 stimulation test using one dose of rhGH [41], it is consistent with findings using longer courses of rhGH. Leptin concentrations were reduced by 20% after 10 days of GH therapy in short children [42], and by 60% after 3 months of rhGH treatment in children with Prader-Willi syndrome, independently of changes in body composition [43]. Higher circulating leptin concentrations have been found in preterm infants on day 1 of life compared to control infants, with a rapid decline after birth, suggesting a physiological advantage by limiting body energy expenditure for subsequent growth [44].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are contradictory results in the literature. Some studies have reported a decrease in leptin levels in short children with [45,46] and without [42] GH deficiency after 1 year of GH therapy. Conversely, Meazza et al [47] have detected a significant increase in leptin levels after 1 year of GH treatment in children with GH deficiency.…”
Section: Discussionmentioning
confidence: 99%